A low complexity detection/decoding algorithm for NB-LDPC coded PRCPM system - Liu, Xiying; Zhao, Shancheng; Ma, Xiao (Physical communication, 2015)
This paper studies the combination of non-binary low-density parity-check (NB-LDPC) codes and M-ary partial response continuous phase modulation (PRCPM). A low-complexity joint detection/decoding algorithm is proposed, which is referred to as the Max-Log-MAP/X-EMS algorithm. In this joint algorithm, the CPM detector is implemented by the Max-Log-MAP algorithm while the LDPC decoder is implemented by the extended min-sum (EMS) algorithms. Three kinds of EMS algorithms, including D-EMS, T-EMS, and M-EMS algorithms, are compared, which are referred to as X-EMS algorithm for convenience. Simulation results show that the Max-Log-MAP/X-EMS algorithm performs as well as the traditional iterative detection/decoding algorithm based on the BCJR algorithm and the q-ary sum–product algorithm, but with lower complexity. In addition, comparison of the proposed NB-LDPC coded PRCPM system with the eBCH coded PRCPM system is given, which shows the performance advantages of our system.